ZnO Quantum Dots: Broad Spectrum Microbicidal Agent Against Multidrug Resistant Pathogens E. coli and C. albicans - Preeti,; Radhakrishnan, V. S.; Mukherjee, Sushanto; Mukherjee, Sujata; Singh, Surinder P.; Prasad, Tulika (Frontiers in Nanotechnology, 2020)
Infectious microbial diseases are leading causes of morbidity and mortality worldwide. Further, emergence of Multidrug resistance (MDR) in microbes has posed a critical concern for public healthcare and microbial therapeutics. Nano-based drug compositions might be ideal candidates to address the challenges of microbial drug resistance. Herein, we synthesized monodispersed, spherical ZnO quantum dots (QDs) of average diameter 5-6 nm as biosafe, nanomicrobicidal agent against MDR pathogens. The broad spectrum microbicidal potential of ZnO QDs was evaluated against Extended Spectrum Beta Lactamase (ESBL) producing MDR isolates of E. coli (with resistance to antibiotics of different classes viz. third & fourth generation of cephalosporin, penicillin, monobactams and quinolones) and MDR isolates of C. albicans (MDR strains had evolved from sensitive strains acquiring resistance). ZnO QDs exhibited dose dependent, broad spectrum microbicidal activity against all MDR isolates of E. coli and C. albicans. Highly reduced growth was observed in all MDR isolates of E. coli and C. albicans at minimum inhibitory concentration (MIC) of 200 µg/ ml ZnO QDs and the growth was further reduced in presence of 250 and 400 μg/ ml of ZnO QDs for E. coli and C. albicans, respectively. To the best of our knowledge, microbicidal potential of ZnO QDs against microbial strains exhibiting MDR for currently used drugs has not been studied. Results of present study indicate that ZnO QDs might be promising as next generation broad spectrum alternative for combating MDR in microbial pathogens.